Study on the influence of career planing and positive psychological capital on subjective career success: Moderating effects of future time perspective and coaching leadership - Oh, EunHye; Tak, JinKook (Korean Journal of Industrial and Organizational Psychology, 2012)
The purpose of this study was to examine the effect of career planning on subjective career success through a mediating variable of positive psychological capital. Further, moderating effects of future time perspective on the relationship between career planning and positive psychological capital and coaching leadership on the relationship between positive psychological capital and subjective career success were examined. Survey was conducted to 316 employees who have been working for more than 3 months at various korean companies. After elimination of inadequate data, 291 data were obtained for further analysis. The results of structural equation analyses showed that career planing had a direct effect on subjective career success and positive psychological capital partially mediated the relationship between career planning and subjective career success. The results of hierarchial regression analyses showed that future time perspective moderated the relationship between career planning and positive psychological capital. Contrary to the hypothesis, however, the relationship between career planning and positive psychological capital was stronger for the low level group of future time perspective. Coaching leadership moderated the relationship between positive psychological capital and subjective career success. Finally, implications and limitations of this study and the directions for future research were discussed on the basis of the results.